Hg2+-induced self-assembly of a naphthalimide derivative by selective turn-on monomer/excimer emissions - Wanichacheva,N. (Elsevier, 2015)
A novel fluorescent sensor bearing two naphthalimide fluorophores based on 2-(3-(2-aminoethylsulfanyl)propylsulfanyl)ethanamine, 1, was readily synthesized for the recognition of Hg2+. The sensitive and selective binding behaviors of 1 were investigated by fluorescence spectroscopy. Sensor 1 selectively binds Hg2+ by exhibiting OFF-ON fluorescence enhancement behaviors of the monomer and excimer bands. The sensor provides excellent Hg2+-selectivity in the presence of high concentrations of competitive ions, particularly Cu2+ and Pb2+ as well as Na+, K+, Mn2+, Cd2+, Ni 2+, Ca2+, Li+, Zn2+ and Co 2+, with an available detection limit of 2.1×10-7 M or 42 ppb. © 2012 Elsevier B.V. All rights reserved.